The Technology of Mobile Banking and Its Impact on the Financial Growth during the Covid-19 Pandemic in the Gulf Region (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to recognize the important factors that influence the adoption of M-banking in gulf region by its users. IT is quantitative research-based the Unified Theory of Acceptance and the Use of Technology that is also known as UTAUT model. With the help of Partial Least-Squares Structure Equation Modeling, the conceptual framework has been tested and designed. The correlation and multiple linear regression analysis have been functioned to obtained results. In gulf region, the adoption of the customers has decreased because of some factors that have been identified in this paper. These factors also decrease the social influence, financial growth and facilitating conditions. The main contribution of this study is to provide a deep understanding of the factors that help to promote the use of mobile banking in some developing countries.  Finally, the research recommends several determinants to use the M-banking in the gulf region setting.